Investigation of the Bitcoin Effects on the Country Revenues Via Virtual Tax Transactions for Purchasing Management - Jumadil Saputra; Rico Nur Ilham; Erlina Erlina; Khairah Amalia Fachrudin; Amlys Syahputra Silalahi; Wahyuddin Albra (International Journal of Supply Chain Management, 2019)
As a consensus network, Bitcoin enables new payment systems and money that are entirely digital or can be interpreted as a virtual currency that uses open source user-to-peer network systems for purchasing and sourcing management. It offers easier way of payment without the need for a bank account, credit card or intermediary. Bitcoin is cash stored in a computer that can be used to replace cash in an online sale transaction. Therefore, this study aims to investigate how to maximize the opportunities that allow Bitcoin in contributing for Indonesia tax revenue and also, the respond to the growing issues of virtual money transactions in the world. This study uses Literature study method based on some previous research and scientific journals that discuss about Bitcoin as a means of payment in sale and purchase transactions. The results of this study Bitcoin transaction tax still needs to be addressed is the absence of Legal Basis and legislation on legality of Bitcoin as a recognized payment instrument in Indonesia. This study can helps the Indonesian governments for creating a guidelines to adjust the regulation of virtual transactions for purchasing management, which have already been created and implemented in other countries and have a positive impact on the country's economy in addition to being one of the sources of increasing state tax revenues.